Medical, morphological and functional aspects of Greek football referees - Rontoyannis, G. P.; Stalikas, A.; Sarros, G.; Vlastaris, A. (The Journal of Sports Medicine and Physical Fitness, 1998)
OBJECTIVE: The aim of the study was to investigate state of health, morphological and functional profile of football referees (Rs). EXPERIMENTAL DESIGN: A prevalence study. PARTICIPANTS: 188 Greek active male Rs of A, B, C and D football divisions have been evaluated. MEASURES: Standard clinical-instrumental and anthropometric methods were used. Appropriate functional tests were used for evaluation of visual performance, physical condition and mental ability. RESULTS: Mean age, height, weight, and BMI were 36.3 +/- 4.5 years, 177.4 +/- 5.7 cm, 81.6 +/- 7.8 kg, and 25.9 +/- 2.1 kg.m-2 respectively. 64% and 6% were overweight and obese respectively. In 27.2% resting blood pressure exceeded upper normal limits. Active (41.5%) and former smokers (17.0%) were identified. Visual acuity and colour discrimination were defective in 2.4% and 0.7% respectively. Stereo depth perception deficiently in 7.1%. Compared to international standards, Rs' mean scores in the 6 physical condition field tests were found satisfactory. All Rs were found efficient in the agility test, two-thirds in the maximal and prolonged speed tests and half of them in the endurance test. Relatively more Rs of A and B divisions were found fit as compared to Rs of C and D divisions. Average IQ score was 112.5 +/- 11.1, while about 90% and 34% of the Rs' IQ score was > or = 100 and > or = 120 respectively. CONCLUSIONS: Average male Greek football R is an apparently healthy, young to middle aged, rather overweight, and functionally efficient. The great majority of Rs of A and B divisions appear better trained and somewhat better functional than Rs of C and D divisions.